Agriculture and the Twofold Relationship between Food Security and Climate Change. Evidence from Romania - Nicolae Istudor; Raluca Andreea Ion; Irina Elena Petrescu; Andrei Hrebenciuc (Amfiteatru Economic)
Nowadays, agriculture is facing a special challenge – to produce more food for a growing population, while reducing greenhouse gas emissions caused by food production. This piece of research is focused on the impact of agriculture on climate change, starting from the assumption that agriculture is affected by climate variability, but also it contributes to it by emitting greenhouse gases, under the restriction of less per capita land. The paper analyses the connection between agricultural emissions and agricultural output, using a simple regression model, which includes variables corresponding to agricultural production and to greenhouse gas emissions. The results of the research highlight the fact that agricultural production has direct effects on greenhouse gas emissions and, thereby, on climate change. The relevance of the research consists in rising awareness of the emergency to integrate climate change in policies and actions related to food security at all levels. Moreover, the paper contributes to the enrichment of scientific literature, because it presents empirical evidence supporting the different effects of agricultural practices on the environment in Romania, with implications for climate change, a scientific direction that has been little studied in other papers